2013
DOI: 10.1111/jns5.12017
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Privigen® in patients with chronic inflammatory demyelinating polyneuropathy: results of a prospective, single‐arm, open‐label Phase III study (the PRIMA study)

Abstract: This prospective, multicenter, single-arm, open-label Phase III study aimed to evaluate the efficacy and safety of Privigen® (10% liquid human intravenous immunoglobulin [IVIG], stabilized with l-proline) in patients with chronic inflammatory demyelinating polyneuropathy (CIDP). Patients received one induction dose of Privigen (2 g/kg body weight [bw]) and up to seven maintenance doses (1 g/kg bw) at 3-week intervals. The primary efficacy endpoint was the responder rate at completion, defined as improvement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
68
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 23 publications
5
68
0
4
Order By: Relevance
“…This was much below the percentage of responsive patients in our negative group (59%) or in reported studies (54%-63%). 1,[22][23][24] Similar observations were reported by a Spanish group, in which none of the 4 patients responded to IVIg. 3 In contrast, beneficial response was noted after plasma exchange in another study.…”
Section: Association Of Cidp With Anti-nf155 Igg4 Antibodiessupporting
confidence: 76%
“…This was much below the percentage of responsive patients in our negative group (59%) or in reported studies (54%-63%). 1,[22][23][24] Similar observations were reported by a Spanish group, in which none of the 4 patients responded to IVIg. 3 In contrast, beneficial response was noted after plasma exchange in another study.…”
Section: Association Of Cidp With Anti-nf155 Igg4 Antibodiessupporting
confidence: 76%
“…Moreover long-term therapy with IGIV-C, showed a maintained improvement in health-related quality of life in patients with CIDP [48]. The PRIMA study [49] confirmed these results with another IVIG 10 % brand.…”
Section: Ivigmentioning
confidence: 62%
“…Another recent prospective, multi-centre, single-arm, open-label Phase III study [Privigen® Impact on Mobility and Autonomy (PRIMA) trial] evaluated the efficacy and safety of IVIG in 28 patients with CIDP [38]. Patients received one induction dose of IVIG (2 g/kg body weight) and up to seven maintenance doses (1 g/kg body weight) at 3-week intervals.…”
Section: Immunomodulation With Intravenous Immunoglobulins (Ivig)mentioning
confidence: 99%